Inside Coca-Cola a CEO's life story of building the world's most popular brand - Isdell, Edward Neville 1944-; Beasley, David 1958- (New York St. Martin's Press, 2011)
A former chairman and CEO of Coca-Cola traces the story of his career, describing his efforts to combat public relations challenges, his contributions to opening markets throughout the world, and his strategies for promoting corporate responsibility.
From Ulster to Africa -- In Johannesburg: my global career is launched -- Conquering Pepsi in the Philippines -- Stagnation in West Germany -- The Wall falls -- Going back to India -- At the helm of Coca-Cola -- Connected capitalism.
Includes bibliographical references and index.
Keywords: Isdell, Edward Neville -- 1944-.; Coca-Cola Company; Chief executive officers -- Biography; Soft drink industry